2011
DOI: 10.1111/j.1758-5740.2011.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with Sling-Wearing after Rotator Cuff Repair and Anterior Shoulder Stabilization

Abstract: Background Compliance with postoperative sling immobilization after shoulder surgery has not been previously studied. In the present study, we examined the compliance with sling-wearing in patients who had had either undergone anterior stabilization or rotator cuff repair.Methods Patients who had undergone either an arthroscopic rotator cuff repair or shoulder stabilization anonymously answered a detailed standardized questionnaire regarding sling-wearing. Routine postoperative instructions require patients to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Patients >60 years of age were found to wear their slings 57.6 hours more per week than younger patients. Nassiri et al 14 similarly showed that patients older than 45 years reported more sling compliance up to 3 weeks postoperatively. Grubhofer et al 7 placed temperature sensors in 54 slings after rotator cuff repair surgery and did not show any associations between sling wear and any patient characteristics.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Patients >60 years of age were found to wear their slings 57.6 hours more per week than younger patients. Nassiri et al 14 similarly showed that patients older than 45 years reported more sling compliance up to 3 weeks postoperatively. Grubhofer et al 7 placed temperature sensors in 54 slings after rotator cuff repair surgery and did not show any associations between sling wear and any patient characteristics.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have attempted to determine the factors associated with sling adherence but have relied on patient-reported sling wear rather than sling wear as measured by a validated temperature-sensing device. 5,14,17 While Silverio and Cheung 17 used the Medical Adherence Measure survey to assess patient-reported adherence, the authors did not address the question related to the sling’s purpose. Nassiri et al 14 assessed sling adherence in patients undergoing rotator cuff repair or shoulder stabilization surgery by sending questionnaires 6 months after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early post-operative mobilisation has been studied extensively in the lower limb [33][34] and has been associated with decreased pain scores, and rapid recovery of muscle function [35][36][37][38]. Early research following rotator cuff repair suggests that although there is no additional benefit of early over delayed postoperative mobilisation integrity of repair is maintained [39].The possibility of earlier safe mobilisation has important implications for the wide range of patients with TASD, for example, poor compliance with immobilisation periods [40], working populations and loss of earnings [41], the psychological and impact of not being engaged in leisure and sport [42], and for older patients, the risk of stiffness due to prolonged immobilisation [43].…”
Section: Discussionmentioning
confidence: 99%